Adapalene-Benzyl Peroxide Combination as an Option for Acne Vulgaris Treatment: A Systematic Literature Review - Rizkia Chairani Asri; Desy Nofita (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background: Acne vulgaris affect 9,4% of the world population, especially in teenage age. Treatment of acne is based on severity; mild acne is treated with a topical agent, whereas moderate and severe acne is treated with topical and systemic agents. Topical therapy, including retinoids, antibiotics, and benzoyl peroxide, is the foundation of acne treatment. Adapalene-benzoyl peroxide therapy can be used in treatment to avoid antibiotic resistance. This study aimed to evaluate the efficacy and tolerance of adapalene/benzoyl peroxide topical treatment in mild to moderate acne vulgaris. Methods: This systematic review conducted a literature search through 3 databases, following PRISMA 2020 guidelines. Inclusion criteria were written in English or Indonesian, published in 2016-2020, a randomized controlled trial (RCT) study designed using human samples, and discussed the efficacy of topical adapalene-benzoyl peroxide in mild and moderate acne vulgaris. Studies that were unavailable in full text and based on secondary data were excluded. Results: Acne vulgaris lesions and scars decreased significantly with adapalene/benzoyl peroxide topical therapy. The addition of moisturizer to therapy can reduce the side effects of retinoate. Conclusion: The combination of adapalene/benzoyl peroxide can be an alternative treatment for mild to moderate acne.